Switch to natalizumab versus fingolimod in active relapsing–remitting multiple sclerosis. Issue 3 (17th January 2015) - Kalincik, Tomas; Horakova, Dana; Spelman, Tim; Jokubaitis, Vilija; Trojano, Maria; Lugaresi, Alessandra; Izquierdo, Guillermo; Rozsa, Csilla; Grammond, Pierre; Alroughani, Raed; Duquette, Pierre; Girard, Marc; et al.
<x xml:space="preserve">Abstract</x> Objective In patients suffering multiple sclerosis activity despite treatment with interferon β or glatiramer acetate, clinicians often switch therapy to either natalizumab or fingolimod. However, no studies have directly compared the outcomes of switching to either of these agents. Methods Using MSBase, a large international, observational, prospectively acquired cohort study, we identified patients with relapsing–remitting multiple sclerosis experiencing relapses or disability progression within the 6 months immediately preceding switch to either natalizumab or fingolimod. Quasi‐randomization with propensity score–based matching was used to select subpopulations with comparable baseline characteristics. Relapse and disability outcomes were compared in paired, pairwise‐censored analyses. Results Of the 792 included patients, 578 patients were matched (natalizumab, n = 407; fingolimod, n = 171). Mean on‐study follow‐up was 12 months. The annualized relapse rates decreased from 1.5 to 0.2 on natalizumab and from 1.3 to 0.4 on fingolimod, with 50% relative postswitch difference in relapse hazard (p = 0.002). A 2.8 times higher rate of sustained disability regression was observed after the switch to natalizumab in comparison to fingolimod (p < 0.001). No difference in the rate of sustained disability progression events was observed between the groups. The change in overall disability burden (quantified as area under the disability–time curve) differed between natalizumab and fingolimod (−0.12 vs 0.04 per year, respectively, p < 0.001). Interpretation This study suggests that in active multiple sclerosis during treatment with injectable disease‐modifying therapies, switching to natalizumab is more effective than switching to fingolimod in reducing relapse rate and short‐term disability burden. Ann Neurol 2015;77:425–435